MODEL OF FAMILY SUBJECTIVE WELL-BEING IN RURAL AND SUB URBAN FAMILIES - Puspitawati, Herien; Sarma, Ma'mun; Herawati, Tin; Yuliati, Lilik Noor; Azizah, Yasmin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
Well-being of family and child can help them to deal with problems that occur in their lives. The main objectives of the study were to analyze using Structural Equation Modeling (SEM) on the examination of the effect of family characteristics and child-parents relations on family and child subjective well-being. This was a census method and a descriptive cross-sectional study design. This study was conducted on highland farmer families living in Cianjur Regency as a typical rural family and the sub-urban of Bogor City boundary as a typical sub urban family. Samples of this study amounted to 203 families consisting of 99 families with males and 104 families with females who were examined through the census method in selected primary schools. There was no significantly difference between the reports of children and mothers to the variables of child and parent relations. However, there was a significantly difference between the child's and mother's reports to the subjective well-being variable with the condition that the child reports higher in subjective well-being for both material and non-material well-being compared to his/her mother's report. The results showed that gender latent variables directly influence the latent variable of child-parent relations. Finally, the latent variable of child-parent relationship had a direct effect on the latent variable of family and children's subjective well-being for both material and non-material.